Isolated small airway reactivity during bronchoprovocation as a mechanism for respiratory symptoms in WTC dust‐exposed community members. Issue 9 (September 2016) - Berger, Kenneth I.; Kalish, Samantha; Shao, Yongzhao; Marmor, Michael; Kazeros, Angeliki; Oppenheimer, Beno W.; Chan, Yinny; Reibman, Joan; Goldring, Roberta M.
Abstract : Introduction: Small airway dysfunction occurs following WTC dust exposure, but its role in producing symptoms is unclear. Methods: Methacholine challenge (MCT) was used to assess the relationship between onset of respiratory symptoms and small airway abnormalities in 166 symptomatic WTC dust‐exposed patients. Forced oscillation testing (FOT) and respiratory symptoms were assessed during MCT. FOT parameters included resistance at 5 and 20 Hz (R5 and R20 ) and the R5 minus R20 (R5–20 ). Results: Baseline spirometry was normal in all (mean FEV1 100 + 13% predicted, mean FEV1 /FVC 80 + 4%). MCT revealed bronchial hyperreactivity by spirometry in 67 patients. An additional 24 patients became symptomatic despite minimal FEV1 change (<5%); symptom onset coincided with increased R5 and R5–20 ( P  > 0.001 vs. baseline). The dose–response of FOT (reactivity) was greater compared with subjects that remained asymptomatic ( P  < 0.05). Conclusions: FOT during MCT uncovered reactivity in small airways as a mechanism for respiratory symptoms in subjects with inhalational lung injury. Am. J. Ind. Med. 59:767–776, 2016. © 2016 Wiley Periodicals, Inc.